764 Prevalence and clinical implications of cardiac involvement in individuals with paucisymptomatic SARS-CoV-2 infection. (8th December 2021) - Trancuccio, Alessandro; Mazzanti, Andrea; Kukavica, Deni; Arnò, Carlo; Sturla, Matteo; Marino, Maira; Bloise, Raffaela; Napolitano, Carlo; Monti, Lorenzo; Priori, Silvia G.
Abstract: Aims: Myocardial involvement has been reported in SARS-CoV-2 infection, especially in hospitalized patients during the acute phase of the disease. However, the exact prevalence and the clinical implications of cardiac involvement in young individuals with paucisymptomatic SARS-CoV-2 infection are debated. Methods and results: We gathered data on 100 young patients with previous paucisymptomatic SARS-CoV-2 infection, not undergoing hospitalization and without previous diagnosis of structural heart disease, who underwent cardiological evaluation in our clinic at IRCCS ICS Maugeri (Pavia, Italy). Results were validated in an external cohort of 28 patients who underwent cardiac magnetic resonance (MRI) at Humanitas Research Hospital (Rozzano, Italy). The study population included 100 patients with previous paucisymptomatic SARS-CoV-2 infection: 60 (60%) males; median age 36 years (IQR: 22–50 years); median time after SARS-CoV-2 infection 181 days (IQR: 76–218 days). At the cardiological evaluation, 31/100 (31%) of patients referred cardiological symptoms, including dyspnoea, palpitations, chest pain or syncope. Overall, 26/100 (26%) patients showed on or more of the following instrumental alterations at first level assessment: 4/100 (4%) increase of TnI; 7/100 (7%) electrocardiographic abnormalities, 12/100 (12%) ventricular arrhythmias, and 11/100 (11%) echocardiographic abnormalities. Of 32 patients who underwent cardiac MRI, myocardial involvement was detected in 6/32 (19%) patients (Figure 1 ), similarly to what was observed in the validation cohort [54% males; median age 47 years (IQR: 26–55 years); myocardial involvement at MRI 4/28, 14%]. Furthermore, the proportion of patients with myocardial involvement was significantly higher in patients with first-level cardiac alterations (6/18, 28%) as compared with patients without cardiac alterations at first-level examination (0/14, 0%, P = 0.024). When analysing possible predictors for the occurrence of cardiac involvement at the MRI, documentation of ventricular arrhythmias at Holter ECG or exercise test was associated with an 87-fold higher probability of cardiac involvement at the MRI (OR: 87.3; 95% CI: 4.0–1914.3; P < 0.001). Conclusions: Around 15–20% of patients with paucisymptomatic SARS-CoV-2 infection exhibit cardiac involvement documented at the cardiac MRI after a mean of 6 months from the onset of the disease. The presence of instrumental alterations detected with first level diagnostic tests, and in particular the documentation of ventricular arrhythmias at the 24 h-Holter ECG or at the exercise stress test, is a powerful predictor of myocardial involvement.